F8 Hippocampal abnormalities in premanifest and early stage huntington's disease. (13th September 2016) - Harris, Kate; Mason, Sarah; Barker, Roger
Abstract : Aims: To assess hippocampal-dependent spatial memory and perception in pre-manifest and early stage Huntington's disease (HD) patients. Background: Huntington's disease (HD) is an autosomal neurodegenerative disorder caused by a CAG repeat expansion in the gene (HTT) which encodes the huntingtin protein (HTT). Although HD is typically considered a motor disorder, cognitive and affective disturbances often precede motor symptoms. Degeneration of the striatum and cerebral cortex are universally found in HD. However, accumulating evidence from patients and animal models suggests that hippocampal dysfunction may be an early feature of the disease, contributing to the cognitive and affective disturbances. The Four Mountains Test is a recently developed measure of hippocampal-dependent spatial cognition and memory. The test has been shown to elicit a characteristic pattern of impairment that is capable of dissociating Alzheimer's disease from Frontotemporal Dementia. Crucially, hippocampal atrophy is observed in the early stages of Alzheimer's disease whilst this region is spared in Frontotemporal Dementia. Methods: Patients were recruited from our research clinic at the Cambridge Centre for Brain Repair. Control participants included the spouses of patients or individuals recruited through an advertisement. We administered the Four Mountains Task to 30 HD patients (pre- manifest and early disease), 50 patients with Parkinson's disease (early and late stage disease) and 80 age and gender matched healthy controls. Results: Patients with Huntington's disease performed significantly worse than healthy controls on the Four Mountains Test, a result which was still significant after age and gender were controlled for. Interestingly, patients with early stage HD were significantly more impaired than pre- manifest patients. The performance of HD patients did not differ from Parkinson's patients, who also performed significantly worse than controls. Conclusion: HD patients exhibited progressive deficits in hippocampal-dependent spatial cognition. The results support evidence showing that hippocampal deficits are present in early stages of the disease and are likely to contribute to aspects of cognitive dysfunction. The results of this study suggest a common hippocampal deficit in Huntington's disease and Parkinson's disease that may be a result of the reciprocal relationship between the striatum and hippocampus.